Improving compostable plastic disposal: An application of the Behaviour Change Wheel intervention development method - Allison, Ayşe Lisa; Purkiss, Danielle; Lorencatto, Fabiana; Miodownik, Mark; Michie, Susan (Frontiers in sustainability (Lausanne), 2022)
Compostable plastics have great potential environmental benefits, however, the damage caused by incorrect waste management offsets them. This study aims to develop a behavior change intervention aimed at improving compostable plastic disposal. We illustrate application of the Behaviour Change Wheel framework to design an intervention in this context. First, the target behavior was understood by specifying it and identifying potential behavioral influences. Second, behavioral influences were systematically linked to potential intervention strategies and refined by evaluating the likely affordability, practicability, effectiveness, acceptability, equity and potential for side-effects (APEASE criteria) in a UK implementation context. Finally, intervention content and implementation options were selected by systematically selecting specific Behavior Change Techniques and refining them by evaluating them against APEASE criteria. The target behavior was identified as UK citizens disposing of compostable plastic waste in the food waste bin meant for collection by local authorities. Influences on compostable plastic disposal were identified as “psychological capability” (i.e., attention and knowledge), “reflective motivation” (i.e., beliefs around environmental impact of compostable plastics) and “physical opportunity” (i.e., access to appropriate waste management). “Education” and “environmental restructuring” were the intervention types selected. “Communications/marketing”, “guidelines” and “restructuring the physical and social environment” were the policy options selected. Selected behavior change techniques were: instruction on how to perform the behavior, prompts/cues, adding objects to the environment and restructuring the physical environment. The resulting intervention is a disposal instruction label for compostable packaging, comprising of instructions and a logo. The next step is user testing the developed disposal instruction labels in terms of their effect on promoting the desired disposal behavior. The novelty of this study includes the development of an intervention to reduce compostable plastic waste and the explicit, step-by-step documentation of the intervention development process. The scientific significance is therefore both applied and theoretical. When evaluated, our intervention has the potential to yield insights relating to what improves compostable plastic disposal amongst citizens. This, in turn, has key policy implications for product and package labeling. By openly documenting our method, we demonstrate a systematic and transparent approach to intervention design, providing an adaptable template and model for others.